The world in 2050 : four forces shaping civilization's northern future - Smith, Laurence C. (New York : Dutton ; Penguin, 2011)
"A vivid, scientifically based forecast of our planet in forty years, distilling cutting edge research into these world-changing forces: demographic trends; natural resource demand; climate change; globalization"--Jacket flap.
What kind of world are we leaving for our children and grandchildren? Geoscientist Laurence Smith draws on the latest global modeling research to construct a sweeping thought experiment on what our world will be like in 2050. The result is both good news and bad: Eight nations of the Arctic Rim (including the United States) will become increasingly prosperous, powerful, and politically stable, while those closer to the equator will face water shortages, aging populations, and crowded megacities sapped by the rising costs of energy and coastal flooding. Smith combines the lessons of geography and history with state-of-the-art model projections and analytical data--everything from climate dynamics and resource stocks to age distributions and economic growth projections. But Smith offers more than a compendium of statistics and studies--he spent fifteen months traveling the Arctic Rim, collecting stories and insights that resonate throughout the book.--From publisher description.
Flying into Fort McMurray -- Martell's hairy prize -- The push. A tale of teeming cities -- Iron, oil, and wind -- California browning, Shanghai drowning -- The pull. Two weddings and a computer model -- One if by land, two if by sea -- The third wave -- Good-bye harpoon, hello briefcase -- Alternate endings. The Pentagon report -- The new north.
Includes bibliographical references (p. 263-307) and index.
BIGD
Keywords: Global environmental change -- Forecasting; Climatic changes -- Forecasting; Twenty-first century -- Forecasts